2015
DOI: 10.1155/2015/687541
|View full text |Cite
|
Sign up to set email alerts
|

Weaker Self-Esteem in Adolescence Predicts Smoking

Abstract: Background. To study whether weaker self-esteem in adolescence is connected with smoking behavior in adulthood. Methods. An age cohort born in 1979 responded to the Lawrence Self-Esteem Questionnaire (LAWSEQ) at the age of 16 (n = 1,072). Respondents' smoking behavior was monitored annually during adolescence and 75.3% (n = 813) of them remained nonsmokers during adolescence. A follow-up questionnaire eliciting smoking behavior was sent to the adolescent nonsmokers at the age of 29 years. Response rate at foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Developmentally, the adolescent brain and body undergo rapid changes, including the establishment of new neuronal connections based on a cascade of new experiences and dramatic hormonal changes that may produce a period of vulnerability to psychiatric disorders 3. Moreover, adolescents may cope with new stresses by developing harmful habits and risky behaviors, including tobacco cigarette smoking (referred to as simply smoking from here forward) 4,5. There is a strong association between smoking and psychiatric disorders, though the nature of this association is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Developmentally, the adolescent brain and body undergo rapid changes, including the establishment of new neuronal connections based on a cascade of new experiences and dramatic hormonal changes that may produce a period of vulnerability to psychiatric disorders 3. Moreover, adolescents may cope with new stresses by developing harmful habits and risky behaviors, including tobacco cigarette smoking (referred to as simply smoking from here forward) 4,5. There is a strong association between smoking and psychiatric disorders, though the nature of this association is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 In addition, low self-esteem in adolescents increases their smoking tendency during adulthood as well. 15 Moreover, there is a positive relationship between low self-esteem at school and drug abuse, 16 which might be provoked by poor performance at school and low approval of the peers. 17 Nazarzadeh et al found a significant and negative relationship between self-esteem and smoking stages.…”
Section: Introductionmentioning
confidence: 99%
“… 19 On the other hand, Mohammadpoorasl et al found no significant relationship between self-esteem and progress at smoking stages 20 and between low self-esteem of adolescence and smoking during adulthood. 15 …”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies about the relationship of self-esteem and smoking conducted in adolescents have been cross sectional 20, 21 and cohort 22, 23 studies. Identification of the causal impact of self-esteem on smoking stages faces seemingly insurmountable problems in observational data, where self-esteem is not manipulable by the researcher and cannot be assigned randomly [24].…”
Section: Introductionmentioning
confidence: 99%